Practitioner and digitally delivered interventions for reducing hazardous and harmful alcohol consumption in people not seeking alcohol treatment: a systematic review and network meta‐analysis. (7th August 2022) - Beyer, Fiona R.; Kenny, Ryan P. W.; Johnson, Eugenie; Caldwell, Deborah M.; Garnett, Claire; Rice, Stephen; Simpson, Julija; Angus, Colin; Craig, Dawn; Hickman, Matt; Michie, Susan; Kaner, Eileen F. S.
Abstract: Aim: To compare the effectiveness of practitioner versus digitally delivered interventions for reducing hazardous and harmful alcohol consumption. Design: Systematic review and network meta‐analysis comprising comprehensive search for randomised controlled trials, robust screening and selection methods and appraisal with the Cochrane Risk of Bias tool. Network meta‐analyses were conducted in Stata using random effects, frequentist models. The confidence in network meta‐analysis (CINeMA) tool was used to assess confidence in effect sizes. Setting: Online or community or health settings where the intervention was immediately accessible without referral. Participants: Non treatment‐seeking hazardous or harmful drinkers. Measurements: Primary outcome was mean difference in alcohol consumption (g/wk); secondary outcome was number of single high intensity drinking episodes. Baseline consumption was analysed as a covariate. Findings: Of 201 included trials (94 753 participants), 152 reported a consumption outcome that could be converted to grams/week; 104 reported number of single high intensity drinking episodes. At 1 and 6 months, practitioner delivered interventions reduced consumption more than digitally delivered interventions (1 month: −23 g/wk (95% CI, −43 to −2); 6 months: −14 g/wk [95% CI, −25 to −3]). At 12 months there was no evidence of difference between practitioner and digitally delivered interventions (−6 g/wk [95% CI, −24 to 12]). There was no evidence of a difference in single high intensity drinking episodes between practitioner and digitally delivered interventions at any time point. Effect sizes were small, but could impact across a population with relatively high prevalence of hazardous and harmful drinking. Heterogeneity was a concern. Some inconsistency was indicated at 1 and 6 months, but little evidence was apparent at 12 months. Conclusion: Practitioner delivered interventions for reducing hazardous and harmful alcohol consumption are more effective than digitally delivered interventions up to 6 months; at 12 months there is no evidence of a difference.